Desenvolvimento de presunto cozido pré-fermentado adicionado de fibra e cloreto de potássio - Baldissera, Eliana Maria (2007)
This work was as subject develop a new carneo product, named ham pre-fermented added of fiber and potassium chloride. The propose experiment was about three differents treatments, treatment 1 with standard wording also named of parcial control treatment 2, with the composition from treatment 1 with parcial substitution of sodium chloride by potassium chloride and add of insoluble wheat fiber and treatment 3 also composition of treatment 2, has initiated culture of Staphylococcus xylosus. The pieces was vaccum packed and submitted to ten days of fermentation to 5º C. The next step was made the cooking and after the stockpile accompaniment for 60 days. During the fermantation was make PH and microbiological analysis (mesophilic, psychrophilic, Micrococcacea e Staphylococcus xylosus). During the stockpile was made the same microbiological analysis of fermentation, physicochemical (pH, color, composition centesimal and minerals) and sensory analysis (color, aroma, texture and accepted). The PH values during the fermentation presented in the track starter add develop (up to 5.4). The starter culture added to treatment 3, presented significant growth (p<0,05) in the period of fermentation and the develop of this organism produce improvement confirmed by sensory assessment. The KCI added and what fiber don´t prejudiced the treatments 2 and 3, then already make possible a gain of potassium, that can be a benefit to hipertensive consumers. However, significantly (p<0,05), the control treatment presented life util with microbiologicals minors counts.